33. FACTORS INFLUENCING THE NUTRITIONAL STATUS OF THE ELDERLY AT EA H’LEO DISTRICT HEALTH CENTER, DAK LAK PROVINCE, 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze factors associated with the nutritional status of the elderly at Ea H’Leo district Health Center in 2022.Methods: A cross-sectional descriptive study was conducted on 251 elderly individuals visiting Ea H’Leo district Health Center from June to September 2022. Convenient sampling and the MNA-SF tool were used to evaluate the nutritional status of the participants. Multivariate logistic regression was employed to identify factors associated with their nutritional status.Results: Among 251 participants, the total MNA score was 22.5. The health risks of the elderly were primarily concentrated in the 70-79 age group. Females had a 0.56 times lower risk compared to males. Elderly individuals from ethnic minorities had a 2.26 times higher risk compared to the Kinh ethnicity group. Those who were employed had a 2.31 times higher risk compared to retirees. Individuals with an income above 10 million VND/month were 7.95 times more at risk compared to those with an income below 5 million VND/month. Participants with moderate physical activity levels had a 1.87 times higher risk compared to those with light activity levels.Conclusion: Factors associated with the nutritional status of the elderly include demographic characteristics, the number of comorbidities, oral health status, chewing and swallowing ability, smoking and alcohol consumption habits, regular exercise, and physical activity levels.
Keywords: Elderly; malnutrition; Ea H’Leo district